Effect of body movements in the venous blood flow and lymphatic circulation - Pinto-Ferreira, Eduardo (Open Science Journal, 2021)
The studies of ballistocardiography about the effect of cardiovascular activity in body motion raised the author interest in the research of the influence of body movements in the circulatory flow in venous and lymphatic vessels. These effects follow Sir Isaac Newton laws. With the body movement, the one-way valve structure of these vessels will cause a mobilization of venous blood and lymph to the proximal side. A model was built to demonstrate the effect of oscillatory movement in a liquid flow in a system of one-way valve. There was a rise of the liquid with difference in level that ranged from 9 cm up to 34 cm, depending on the amplitude and frequency. The model tried to mimic a segment of vein with its valve, and evaluate the effectiveness of oscillatory movements in the progression of the liquid, In a preliminary study, to assess the effect of oscillatory movements on leg swelling, this movements was applied in a clinical cases. There was regression of the oedema and circumference on the leg, by oscillatory movements, that was correlated with increase in lymphatic and venous drainage. Venous stasis is a predisposing factor of venous thromboembolism. How we extrapolate from the experimental model, the oscillatory movements of the legs improving venous circulation may contribute to the prophylaxis of venous thromboembolism. In conclusion, it is of interest to study its application in some situations of venous thromboembolism risk.